The importance of wild resources as a reflection of the resilience and changing nature of early agricultural systems in East Asia and Europe - Stevens, Chris J.; Crema, Enrico R.; Shoda, Shinya (Frontiers in Ecology and Evolution, 2022)
We examine the changing importance of wild starch rich plant staples, predominantly tree nuts, in early agricultural societies in East Asia and Europe, focusing on Korea, Japan, and Britain. A comparative review highlights variations in the importance of wild plant staples compared to domesticated crops. The Korean Middle to Late Chulmun periods (c.3500-1500 BC) was characterized by a high reliance on nuts alongside millet. This declines with the transition to rice agriculture, but remains significant during the Mumun period (c. 1500-300 BC). In Japan, the arrival of rice and millets in the Yayoi Period (c.1000 BC -250 AD) saw continued evidence for high levels of reliance on wild resources, which declines only in the Kofun and early historical periods. In Early Neolithic Britain (c.4000-3300 BC) cereal agriculture is accompanied by high evidence for wild plant foods. But during the Middle to Late Neolithic (3300-c.2400/2200 BC) cereals were abandoned on the mainland with hazelnuts becoming a prominent plant staple. Agriculture returned in the second half of the 3rd millennium BC, followed by a strong decline in wild plant food use during the Middle to Late Bronze Age (1700-700 BC). Such patterns have previously been attributed to the slow adoption of farming by indigenous peoples, with a continued reliance on wild resources. In light of evidence demonstrating that the dispersal of agriculture was largely driven by a mixture of demic-diffusion and introgression of hunter-gatherers into agricultural groups, a reinterpretation of the role of wild foods is needed. It is argued that the relative importance of wild plant staples provides an indicator of the stability and dependability of agricultural and social systems. A heavy reliance on wild foods in early agricultural societies is tied to the slow adaptation of domesticated crops to new environments, where agricultural and social landscapes are yet to be firmly established, and social systems that could mitigate for poor harvests and storage were often absent. The retained lengthy persistence of wild plant staples in East Asian subsistence systems compared to the British Isles likely reflects differences in the ecological and labor demands for rice compared to Western Asiatic cereals.